Storage and release of acetylcholine in a sympathetic ganglion - Birks, R. I. (1974)
1. The hypotheses of preferential release of newly synthesized acetylcholine (ACh) and two compartment storage of transmitter in the cat superior cervical ganglion have been re-examined by testing, first, the assumption that ganglionic ACh stores do not alter during a 20 min rest following 60 min preganglionic nerve stimulation at 20/s, and secondly, the implication that the rate of ACh release should be high near the onset of activity and decline to a lower rate with time irrespective of the frequency of stimulation. 2. The ganglionic ACh stores were found to increase by 38 ± 8% within 20 min following 60 min preganglionic nerve stimulation at 20/s, and this extra ACh was releasable. 3. The rate of ACh release from ganglia perfused with cat plasma and stimulated at 4/s increased over the first 5 min of stimulation to reach a 27% higher rate that was maintained. 4. Correction of the original data to allow for the post-activation increase in ACh stores suggests that newly synthesized ACh equilibrates with most of the preformed stores. The time course of ACh release at 4/s does not support the two compartment model as currently formulated. 5. These findings resolve in part a conflict between the physiological data and a recent hypothesis for ACh storage based on ganglion morphology.